ASPEK SOSIAL DALAM NOVEL LAMPUKI KARYA ARAFAT NUR - Hartanto, Heri; Sutejo; Suprayitno, Edy (STKIP PGRI Ponorogo Press, 2021)
Lampuki novel is a literary work that describes Aceh at the time after the fall of President Soeharto. It contains social aspects such as education, economy and religion. This study aims to describe the socio-educational, economic, and religious aspects of Arafat Nur>s novel Lampuki (2019) by using the sociological theory of literature as a tool of analysis. The research method used in this research is a descriptive qualitative method using the library technique, observe and take notes. The technique used in this study is a qualitative technique, while to analyze the data the researcher used genetic dialectic method. The results of the analysis show that the social aspects in Lampuki>s novel are socio-educational, economic, and religious aspects. The education aspect describes the existence of education at school, at home, and outside of home. The socio-economic aspect illustrates the difficulty of the community in getting income and employment. The social aspect of religion discusses the relationship between the individual and God, and the individual and society.